Violation Maxim of Quantity Found in â€œWednesdayâ€ Movie Series - ANGGRENI, NI MADE ARI (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research aims to analyze the violations of the cooperative principle, especially maxims of quantity in the Movie Series entitled Wednesday. Cooperative principles theorized by Grice (1975) explained how people use the language well and efficiently. This study used the descriptive qualitative method to analyze the data. The researcher collected the data in three ways: first watching the movie repeatedly to know the specifics of the conversation among the characters, second, observing the dialogue by taking notes. Third is sorting out the correct maxim quantity that can be analyzed. The result of this study shows five per utterance characters that violated the maxim of quantity. This happens because the context of the movie which is a mystery genre refers to the situation of the characters taking excessive or exceeding normal actions to solve a mystery that occurs in the Nevermore school. This study is useful whether in presentations, discussions, or even writing to understanding the Cooperative Principle helps us convey our messages clearly, concisely, and relevantly so that they can be easily understood by listeners.